Elisabeth Schüssler Fiorenza: within or beyond the Third Quest for the historical Jesus? - Walters, Amy (2020)
The quests for the historical Jesus have seen a number of developments in the ways in which we study Jesus, and in the conclusions we come to about his life and influence. One of these developments has been the increased number of feminist publications, in part driven by Elisabeth Schüssler Fiorenza. Schüssler Fiorenza’s work looks to uncover the reality of Christianity’s kyriarchal origins, and to encourage her peers to engage in historical Jesus research that is self-evaluating. These concerns are also evident in the work of other Third Quest feminist researchers who recognise the negative impact of continued patriarchal publications on the lives of women today. Through an evaluation of Schüssler Fiorenza’s work on fundamentalism, feminism, and anti-Semitism, this dissertation situates Schüssler Fiorenza’s work and that of other feminist researchers within the quests and asks whether the Third Quest was ready for the work of Elisabeth Schüssler Fiorenza. The reformative and critical work of Schüssler Fiorenza, like that of her fellow feminist researchers, often goes uncited, despite its value in problematising historical Jesus research. By comparing the work of prominent Third Questers with that of Schüssler Fiorenza et al., this dissertation finds cause to propose the existence of a Third Quest Critical-Stream, whereby feminist researchers not only contribute to malestream scholarship but also engage in work that looks to inform and improve the state of the Third Quest.